Anastasia candre: nɨmairango—woman of knowledge—in yuakɨ murui-muina (2014)
This article deals with Anastasia Candre Yamacuri’s research about the ritual of the fruits (yuakɨ), in her unpublished text Yuakɨ Murui-Muina: cantos del ritual de frutas de los uitoto (songs of the ritual of the fruits of the Uitoto). In the first part, it presents Anastasia as a nɨmairango, woman of knowledge, from her autobiographical introduction, and discusses the difficult relationships between production of knowledge and gender for an indigenous woman living in the city. Then, it addresses two aspects of her research about the ritual of the fruits: the meaning and structure of the ritual and an approach to the interpretation of a song of divination of the jaiokɨ variety. Finally, it refers briefly to the paintings elaborated by Anastasia to illustrate de the process of the ritual of the fruits.